Luka innowacyjna między Polską a krajami Unii Europejskiej - Jahn, Joanna (Innovation Gap between Poland and European Union Countries, 2006)
The article includes the review of innovation indicators presented by European Innovation Scoreboard and the Growth Innovation Index. There are also data concerning the level of innovativeness of enterprises in Poland and in the new countries in the European Union.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 213-224